2019
DOI: 10.1111/bjd.17917
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association studies and polygenic risk scores for skin cancer: clinically useful yet?

Abstract: Summary Background Genome‐wide association studies (GWAS) have identified thousands of susceptibility variants, although most have been associated with small individual risk estimates that offer little predictive value. However, combining multiple variants into polygenic risk scores (PRS) may be more informative. Multiple studies have developed PRS composed of GWAS‐identified variants for cutaneous cancers. This review highlights data from these studies. Objectives To review published GWAS and PRS studies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 71 publications
1
38
0
Order By: Relevance
“…Despite the individual magnitude of association for each SNP being small, they can be used in aggregate to characterize the genetic liability toward disease outcomes through a polygenic risk score (PRS). These scores have substantial clinical utility for disease (in this case, KC) prediction (Roberts et al, 2019). Previous studies have shown that PRSs, in combination with conventional risk factors, can provide useful information for risk stratification for common complex diseases such as cancers (Dai et al, 2019;Mavaddat et al, 2019;Seibert et al, 2018) and cardiovascular disease (Abraham et al, 2019;Inouye et al, 2018;Khera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the individual magnitude of association for each SNP being small, they can be used in aggregate to characterize the genetic liability toward disease outcomes through a polygenic risk score (PRS). These scores have substantial clinical utility for disease (in this case, KC) prediction (Roberts et al, 2019). Previous studies have shown that PRSs, in combination with conventional risk factors, can provide useful information for risk stratification for common complex diseases such as cancers (Dai et al, 2019;Mavaddat et al, 2019;Seibert et al, 2018) and cardiovascular disease (Abraham et al, 2019;Inouye et al, 2018;Khera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…An increased melanoma risk has been documented in carriers of germline mutations causing other cancer syndromes, including hereditary breast and ovarian cancer ( BRCA1/BRCA2 ), retinoblastoma ( RB1 ), or xeroderma pigmentosum ( XPs ) [ 16 ]. The low-risk group includes variants in genes coding for proteins involved in melanogenesis (MC1R, MITF, OCA2, SLC45A2, TYR, TYRP1) and other processes (ASIP, CASP8, MTAP, OBFC1), revealed dominantly by genome-wide association studies (GWAS) [ 17 , 18 , 19 ]. The identification of individuals carrying germline mutations in melanoma-predisposition genes enables their tailored surveillance with an early detection of melanoma and other associated tumors, and with genetic counselling for their relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Their thorough review maps the literature of genetic/PRSs including assessment of the populations and other clinical and phenotypic characteristics used. In one included study, for example, a 204‐single‐nucleotide polymorphism PRS model using data from a large GWAS meta‐analysis in melanoma and validated in a Southern European population showed a c‐statistic of 64·4%, with an up to 7% increase in the risk predictive ability for melanoma compared with when using only traditional phenotypic risk factors . The PRS‐based c‐statistic in this model was larger than those observed in other cancers, for example lung cancer (56·4%) and breast cancer (61·5%) and is equivalent to PRS models for prostate cancer (65·4%), suggesting that for cancers with a strong heritable component such as melanoma and prostate cancer, PRS can improve risk prediction and help identify individuals at risk who may benefit from increased surveillance …”
mentioning
confidence: 93%
“…The paper by Roberts et al . in this issue of the BJD reports a systematic approach and comprehensive evaluation of all currently available data from 21 GWAS and 11 PRS studies in melanoma and epithelial skin cancers (basal cell carcinoma and squamous cell carcinoma) .…”
mentioning
confidence: 99%